Biennial review of health care management meso perspective - Savage, Grant T. 1954-; Fottler, Myron D. (Advances in health care management, 2009)
This proposed volume will provide state-of-the art reviews of health care management, linking concerns about health care workforce management with health care organization management issues. This meso perspective, linking micro and macro organizational processes, should appeal to health care management researchers and doctoral students. Review articles in this volume will orient new and established scholars about current themes within health care management, as well as emerging themes and divergent views. The authors evaluate these future directions and offer their perspective on the direction or directions that would help build theory and improve the practice of health care management. Specifically, the volume will focus both on health care workforce management issues, including allied health professionals, nurses, and physicians, and on health care organization management issues, ranging from organizational governance and strategy to the globalization of health care organizations.